MULTIMEDIA LEARNING IN HEALTH EDUCATION: HOW AUDIOVISUAL MEDIA IMPROVE PSYCHOMOTOR SKILL DEVELOPMENT IN MASSAGE TRAINING - Syampurma, Hilmainur; Sasmitha, Weny; Effendi, Hastrya; Selvani, Arif Selfa (Curricula: Journal of Teaching and Learning, 2026)
More than 50% of students enrolled in the massage course during the 2022/2023 academic year failed to meet expected competency standards, with deficiencies identified in practicum performance, technical precision, procedural comprehension, and fine motor skills. This study investigated the effectiveness of audiovisual instructional media in enhancing massage skill acquisition among vocational education students. Grounded in multimedia learning theory, audiovisual media are posited to facilitate efficient knowledge transfer by integrating visual demonstration with auditory explanation, thereby supporting cognitive processing and psychomotor development. A quasi-experimental design with a post-test-only control group was employed. The sample comprised 108 students, randomly assigned to an experimental group receiving audiovisual-based instruction and a control group receiving conventional demonstrations. Massage competency was assessed using a structured observation sheet evaluating technical accuracy, procedural sequence, and motor coordination. Data normality was confirmed via the Shapiro–Wilk test, followed by an independent-samples t-test for group comparison. Results revealed that the experimental group achieved a significantly higher mean score (M = 87.92, SD = 3.863) compared to the control group (M = 83.52, SD = 5.215), with a statistically significant difference (t = 4.87, p < 0.001). These findings demonstrate that audiovisual instructional media positively influence students' mastery of massage skills by enhancing procedural clarity, reducing cognitive load, and enabling repeated visual rehearsal. The study concludes that integrating audiovisual resources into vocational health curricula can effectively address competency gaps and improve practical skill outcomes. Educators and curriculum designers are encouraged to adopt multimodal instructional strategies to support psychomotor learning in competency-based education contexts.